2012
DOI: 10.1094/pdis-03-12-0303-re
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Spring Wheat Germplasm for Resistance to Bacterial Leaf Streak Caused by Xanthomonas campestris pv. translucens

Abstract: Kandel, Y. R., Glover, K. D., Tande, C. A., and Osbome, L. E. 2012. Evaluation of spring wheat germplasm for resistance to bacterial leaf streak caused by Xanthomonas campestris pv. translucens. Plant Dis. 96:1743-1748.Bacterial leaf streak (caused by Xanthomonas campestris pv. translucens) has reemerged as a potential threat in spring wheat {Triticum aestivum) production areas in the northern Great Plains. As with other foliar bacterial diseases, chemical control under field situations is neither economical n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 15 publications
(18 reference statements)
2
25
0
Order By: Relevance
“…Nearly all methods utilized for inoculation, resistance evaluation, and data collection in the disease nurseries were consistent with those routinely employed by the SDSU-HRSW breeding program [18,19] [19].…”
Section: Disease Evaluationmentioning
confidence: 83%
“…Nearly all methods utilized for inoculation, resistance evaluation, and data collection in the disease nurseries were consistent with those routinely employed by the SDSU-HRSW breeding program [18,19] [19].…”
Section: Disease Evaluationmentioning
confidence: 83%
“…where y i = the number of leaflets with brown spot per pot at observation time and t i+1 -t i denotes number of days between the subsequent observation dates (Kandel et al 2012).…”
Section: Figurementioning
confidence: 99%
“…Because no chemical control is available, host resistance appears to be the only way to control wheat BLS. Several sources of BLS resistance have been identified in diverse wheat or barley germplasm and related species (Hagborg, ; Akhtar and Aslam, ; Duveiller et al , ; Alizadeh et al , ; El Attari et al , ; Milus et al , ; Tillman et al , ; Adhikari et al , ; Kandel et al , ; Sapkota et al , ). These studies revealed a low percentage of resistant lines and no immune or highly resistant materials were found in the wheat germplasm.…”
Section: Genetics and Mapping Of Host Resistancementioning
confidence: 99%
“…Since then, BLS has been found in many places in the United States with outbreaks and epidemics mostly having occurred in the southeastern regions (Milus and Mirlohi, 1994;Tubajika et al, 1999). In recent years, the incidence of BLS has increased in the Upper Midwest region of the United States, including North Dakota, Minnesota, and South Dakota (Adhikari et al, 2012a;Kandel et al, 2012;Curland et al, 2018).…”
Section: Introductionmentioning
confidence: 99%